State Authorities As Subject Of Obligation Relations Arising From Damage - Nuriddin Kuldashev (Peerian Journals Publishing, 2023)
The article describes the issues related to the participation of state bodies as a "state institution" and a "legal entity" in liability relations arising from damage (hereinafter referred to as "delict relations"). Also, the tort liability of state institutions is explained. It is justified in which cases the obligation of state bodies to compensate the damage is assigned to the state and in which cases to themselves. The opinions expressed by civil scientists on the issue of compensation for damages caused by the illegal decisions and illegal actions (inaction) of the officials of state bodies were analyzed. The legislation of foreign countries, such as Germany, England, Turkey, Ukraine, the Russian Federation and a number of CIS countries, was studied. Proposals and recommendations on improving the mechanism of compensation for damage caused by state bodies have been developed in our national legislation. In order to ensure timely and complete compensation of damage caused to citizens and legal entities by state bodies and their officials in the course of exercising their powers, it was scientifically justified that a special fund of the state should be established.
Keywords: obligations arising from damage; delict liability; damage; compensation